Pengaruh Mobilisasi Dini Terhadap Lamanya Penyembuhan Luka Post Operasi Sectio Caesar di Ruang Kalimaya RSUD Dr. Slamet Garut - Kurniawan Dewi Budiarti; Rita Marlina (STIKes Karsa Husada Garut, 2014)
Caesarea Post operative often lead to complications of non surgical wound. As a general infection or sepsis that may arise due to open wounds or bad state of thepatient so that the body is not able to overcome the resistance of infection and wound healing process is longer. Nursing care patients with postoperative sectio caesareaone of which is the mobilization. The general objective of this study was to determine the effect of early mobilization on the length of postoperative sectio caesarea wound healing in space Kalimaya dr Slamet Garut hospital in 2014. Research methods in use are quasi experiments with sttic design group comparison. Sample use is 40 respondents with direct observation data retrieval techniques and split into two groups: control group and experimental group. The results of the study, postoperative wound healing sectio caesarea not with mobilization is 7 days and the average wound healing time was 4 days with the mobilizatio. In conclusion, no effect of early mobilization with the lengt of postoperative wound healing in space Kalimaya sectio caesarea dr Slamet Garut hospital with Pv 0,000< α 0,05. It is recommended that nurses improve the guidance of early mobilization on mother with postoperative sectio caesarea.